Outcomes in reported penicillin allergic mothers and neonates requiring Group B streptococcal prophylaxis: a retrospective observational cohort study - Justin Kirven; David Beddow; Love Patel; Claire Smith; Katherine S. Booker; Barite Dawud; Catherine A. St. Hill (BMC, 2021)
Abstract Background Infectious morbidity and mortality in the first week of life is commonly caused by early-onset neonatal Group B streptococcus (GBS) disease. This infection is spread from GBS positive mothers to neonates by vertical transmission during delivery and results in serious illness for newborns. Intrapartum prophylactic antibiotics have decreased the incidence of early-onset neonatal GBS disease by 80%. Patients labeled with a penicillin allergy (PcnA) alternatively receive either vancomycin or clindamycin but effectiveness is controversial. We evaluated the influence of a reported PcnA label versus no PcnA label on inpatient maternal and neonatal outcomes. Methods Our goal was to examine the relationship between a PcnA label, maternal and neonatal outcomes, and hospital costs. We collected retrospective data with institutional IRB approval from 2016 - 2018 for hospitalized patients who were GBS positive, pregnant at time of admission, ≥ 18 years of age, received antibiotic prophylaxis for GBS, were labeled as PcnA or non-PcnA, and completed a vaginal delivery. Patient characteristics and maternal/neonatal outcomes were examined. Statistical tests included calculations of means, medians, proportions, Mann-Whitney, two-sample t-tests, Chi-squared or Fisher's Exact tests, and generalized linear and logistic regression models. Significance was set at p < 0.05. Results Most PcnA patients were white, older, had a higher median body mass index and mean heart rate, and a greater proportion used tobacco than non-PcnA patients. In regression analyses, PcnA hospitalized patients received a shorter duration of antibiotic treatment than non-PcnA patients [incidence rate ratio (IRR): 0.45, 95% CI: 0.38-0.53]. PcnA patients were also more likely to have their baby's hospital LOS be > 48 h [adjusted odds ratio (AOR): 1.35, 95% CI: 1.07-1.69] even though the PcnA mothers' LOS was not different from non-PcnA mothers. Cost of care, mortality, intensive care, median parity, mean gravidity, and miscarriage were similar between the groups. Conclusions In hospitalized obstetric patients, a PcnA label was associated with a shorter maternal course of antibiotic treatment and a longer neonatal LOS. Further prospective studies are needed to clarify the underlying reasons for these outcomes.